SELECTIVE APPETITE IN CHILDREN - E. V. Pavlovskaya (Вопросы современной педиатрии)
This literature review summarizes modern data on the issue of selective appetite in children. Selective appetite is a relatively new term, which does not have exact quantitative determinations. To this kind of children (with selective appetite) are usually referred those eating unvaried food and rejecting both known and unknown products. Prevalence of selective appetite in children depends on the used criteria for evaluation of this condition and varies from 8 to 60%. Such peculiarity of eating behavior tends to maintain during all childhood. According to different studies the decrease of intake of almost all macro- and micronutrients was established in children with selective appetite. Chronic nutrients deficiency in children with selective appetite can become a cause of physical development and cognitive dysfunctions. Nutritive support is recommended to such children in order to provide them with appropriate amounts of nutrients and normalize growth processes. Nutritive formula described in this article fulfills the function of «nutritive insurance», providing appropriate and balanced nutrition to children with limited diet. To resolve the problem of selective appetite the combined work of pediatricians, nutritionists and psychologists/psychoneurologists is required.